2006
DOI: 10.1529/biophysj.105.073890
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State NMR Investigation of the Membrane-Disrupting Mechanism of Antimicrobial Peptides MSI-78 and MSI-594 Derived from Magainin 2 and Melittin

Abstract: The mechanism of membrane interaction of two amphipathic antimicrobial peptides, MSI-78 and MSI-594, derived from magainin-2 and melittin, is presented. Both the peptides show excellent antimicrobial activity. The 8-anilinonaphthalene-1-sulfonic acid uptake experiment using Escherichia coli cells suggests that the outer membrane permeabilization is mainly due to electrostatic interactions. The interaction of MSI-78 and MSI-594 with lipid membranes was studied using 31 P and 2 H solidstate NMR, circular dichroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
239
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(277 citation statements)
references
References 52 publications
(66 reference statements)
23
239
0
Order By: Relevance
“…The orientation of 1 at an angle of Ϸ56°to the interface normal suggests that 1 does not operate through a barrel-stave mechanism, because that would require a transmembrane configuration (5). Although it cannot be concluded that 1 exhibits identical mechanistic behavior to natural, ␣-helical antimicrobial peptides, these x-ray results demonstrate ampetoid-lipid interactions consistent with those seen for AMPs such as pexiganan (53) and LL-37 (51).…”
Section: Discussionmentioning
confidence: 54%
“…The orientation of 1 at an angle of Ϸ56°to the interface normal suggests that 1 does not operate through a barrel-stave mechanism, because that would require a transmembrane configuration (5). Although it cannot be concluded that 1 exhibits identical mechanistic behavior to natural, ␣-helical antimicrobial peptides, these x-ray results demonstrate ampetoid-lipid interactions consistent with those seen for AMPs such as pexiganan (53) and LL-37 (51).…”
Section: Discussionmentioning
confidence: 54%
“…The resulting increase in the separation of the anionic lipids allows an increase in the disorder, or cis-trans isomerizations, at the level of the fatty acyl chains that is reflected in the observed reduction-of-order parameter throughout the acyl chain. This model can be compared with a previous study of the membrane insertion of ethanol at the hydrocarbon-water interface (3), where the hydrophobic core of the membrane also becomes disordered, albeit at rather high ethanol concentrations, and a very recent study of the effect of both melittin-and magainin-derived peptides on deuterated phosphatidylcholine (28), where both these peptides adopt an in-plane orientation and disrupt the acyl chain order in a fashion similar to that shown here for the LAH peptides at acidic pH.…”
Section: Discussionmentioning
confidence: 99%
“…The lead 22-mer peptide MSI-78 has 62% helicity, whereas helicity values around 40−45% have been reported by Mercke et al for this peptide when bound to POPC small unilamellar vesicles (SUV). 34,35 For MSI-78(4−20) the determined mean helix content was 33%, which shows a difference of approximately 30% in the helix content between the two peptides. Figure 4D represents the helical wheel projections of the peptides where the relative position of the amino acids and its polar/nonpolar character is displayed.…”
Section: Molecular Pharmaceuticsmentioning
confidence: 95%